Response of the Calanoid Copepod Clausocalanus furcatus, to Atmospheric Deposition Events: Outcomes from a Mesocosm Study - Christou, Epaminondas D.; Zervoudaki, Soultana; Fernandez De Puelles, Ma Luz; Protopapa, Maria; Varkitzi, Ioanna; Pitta, Paraskevi; Tsagaraki, Tatiana M.; Herut, Barak (Frontiers in Marine Science, 2017)
Atmospheric deposition is assumed to stimulate heterotrophic processes in highly oligotrophic marine systems, controlling the dynamics and trophic efficiency of planktonic food webs, and is expected to be influenced by climate change. During an 8-day mesocosm experiment, we investigated the channeling, of the Saharan dust (SD) and mixed aerosols (A) effects on microplankton, up to the copepod trophic level in ultra-oligotrophic Eastern Mediterranean waters. Using mesocosms with SD and A treatments, the feeding response of the dominant copepod Clausocalanus furcatus was assessed every second day. We hypothesised that increased food availability under atmospheric deposition would result in increased copepod ingestion rates, selectivity and production. Overall, no robust pattern of food selection was documented, and daily rations on the prey assemblage of all mesocosms were very low, thereby indicating severe food limitation of C. furcatus. Although increased food availability was not actually true, after a few days, ingestion of ciliates was maximised, followed by egg production, in both the SD and A treatments, indicating their importance in the diet of this copepod as well as a response of C. furcatus feeding performance. Our results help in understanding trophic efficiency of marine food webs in ultra-oligotrophic environments under atmospheric deposition. We suggest that future mesocosm research in oligotrophic waters should consider more than one copepod species.